A national survey of antimicrobial stewardship content in Canadian entry-to-practice pharmacy programs. Issue 1 (3rd May 2023) - Sauve, Jenna M.; Dresser, Linda D.; Rocchi, Marie A.; So, Miranda
Abstract: Objective: To describe the current landscape of antimicrobial stewardship (AMS) instruction in Canadian entry-to-practice pharmacy programs and the perceived barriers and facilitators to optimizing teaching and learning. Design: Electronic survey. Participants: Faculty representatives from the 10 Canadian entry-to-practice pharmacy programs, including content experts and faculty leadership. Methods: A review of international literature pertaining to AMS in pharmacy curricula informed a 24-item survey, which was open for completion from March to May of 2021. Curriculum content questions were developed using AMS topics recommended by pharmacy educators in the United States, and professional roles described by the Association of Faculties of Pharmacy of Canada. Results: All 10 Canadian faculties returned a completed survey. All programs reported teaching AMS principles in their core curricula. Content coverage varied, with programs teaching, on average, 68% of the recommended AMS topics from the United States. Potential gaps were identified within the professional roles of "communicator" and "collaborator." Didactic methods of content delivery and student assessment, such as lectures and multiple-choice questions, were most frequently used. Three programs offered additional AMS content in their elective curricula. Experiential rotations in AMS were commonly offered, though teaching AMS in formalized interprofessional settings was rare. Curricular time constraints were identified by all programs as a barrier to enhancing AMS instruction. A course to teach AMS, a curriculum framework, and prioritization by the faculty's curriculum committee were perceived as facilitators. Conclusions: Our findings highlight potential gaps and areas of opportunity within Canadian pharmacy AMS instruction.